2021
DOI: 10.1021/acs.bioconjchem.1c00042
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Bivalent GalNAc-Conjugated Betulin as a Potent ASGPR-Directed Agent against Hepatocellular Carcinoma

Abstract: Herein, we describe the design, synthesis, and biological evaluation of novel betulin and N-acetyl-d-galactosamine (GalNAc) glycoconjugates and suggest them as targeted agents against hepatocellular carcinoma. We prepared six conjugates derived via the C-3 and C-28 positions of betulin with one or two saccharide ligands. These molecules demonstrate high affinity to the asialoglycoprotein receptor (ASGPR) of hepatocytes assessed by in silico modeling and surface plasmon resonance tests. Cytotoxicity studies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 62 publications
(122 reference statements)
1
12
0
Order By: Relevance
“…In other words, the hepatocyte-targeting capacity followed the W-1-5 (monoga-lactose) < W-2-9 (digalactose) < W-3-8 (trigalactose) order, obeying the rules of the galactose-recognition cluster effect toward ASGPR. Interestingly, it was reported that the galactose-modified bis-fluorophore conjugate, 24 the galactosamine-modified betulin conjugate, 25 and the trivalent galactosamine-modified Cy5 dye 26 showed a similar hepatocytetargeted tendency, also confirming the reliability of our results.…”
Section: ■ Introductionsupporting
confidence: 90%
“…In other words, the hepatocyte-targeting capacity followed the W-1-5 (monoga-lactose) < W-2-9 (digalactose) < W-3-8 (trigalactose) order, obeying the rules of the galactose-recognition cluster effect toward ASGPR. Interestingly, it was reported that the galactose-modified bis-fluorophore conjugate, 24 the galactosamine-modified betulin conjugate, 25 and the trivalent galactosamine-modified Cy5 dye 26 showed a similar hepatocytetargeted tendency, also confirming the reliability of our results.…”
Section: ■ Introductionsupporting
confidence: 90%
“…The receptor was immobilised on the surface of the CM5 sensor chip, as was reported previously. 18,19 Results are presented as equilibrium dissociation constants ( K D , Table 1). The obtained conjugates demonstrated greater affinity to the ASGPR compared to unmodified atorvastatin.…”
Section: Resultsmentioning
confidence: 99%
“…Betulin glycoconjugates obtained as a result of attaching N-acetyl-D-galactosamine fragments to the C-3 or/and C-28 positions in betulin’s molecule also using triazole as a linker were tested in vitro against HepG2 and Huh7 hepatocellular carcinoma cells, PC3 prostate cancer cells, and A549 lung adenocarcinoma cells. The bivalent derivatives, in particular, compound Bet 25, bearing two modified galactosamine fragments at C-3 and C-28, respectively, exerted stronger cytostatic effects against HepG2 cells compared with monovalent glycoconjugates by inducing G0/G1 cell cycle arrest [ 39 ]. In opposition to these findings, Grymel et al, who synthesized a series of betulin glycoconjugates by attaching D-glucose or D-galactose through triazole linkers to the C-3 and/or C-28 positions, reported that the glycoconjugates containing only one sugar unit exhibited equal or lower biological activity compared with the parent compound.…”
Section: Betulinmentioning
confidence: 99%